Epidemic Preparedness—Leishmania tarentolae as an Easy-to-Handle Tool to Produce Antigens for Viral Diagnosis: Application to COVID-19 - Varotto-Boccazzi, Ilaria; Manenti, Alessandro; Dapporto, Francesca; Gourlay, Louise J.; Bisaglia, Beatrice; Gabrieli, Paolo; Forneris, Federico; Faravelli, Silvia; Bollati, Valentina; Rubolini, Diego; Zuccotti, Gianvincenzo; Montomoli, Emanuele; et al. (Frontiers in Microbiology, 2021)
To detect and prevent emerging epidemics, discovery platforms are urgently needed, for the rapid development of diagnostic assays. Molecular diagnostic tests for COVID-19 were developed shortly after the isolation of SARS-CoV-2. However, serological tests based on antiviral antibody detection, revealing previous exposure to the virus, required longer testing phases, due to the need to obtain correctly folded and glycosylated antigens. The delay between the identification of a new virus and the development of reliable serodiagnostic tools limits our readiness to tackle future epidemics. We suggest that the protozoan Leishmania tarentolae can be used as an easy-to-handle micro-factory for the rapid production of viral antigens to face emerging epidemics. We engineered L. tarentolae to express the SARS-CoV-2 Receptor Binding Domain (RBD) and report the ability of the purified RBD antigen to detect SARS-CoV-2 infection in human sera, with a sensitivity and reproducibility comparable to that of a reference antigen produced in human cells. This is the first application of an antigen produced in L. tarentolae for the serodiagnosis of a Coronaviridae infection. Based on our results, we propose L. tarentolae as an effective system for viral antigen production, even in countries that lack high-tech cell factories.